Antecedent of Role Conflict toward Accountant Satisfaction - Evi Yuniarti (Jurnal Ilmiah ESAI, 2011)
The aims of this article are to determine antecedent of role conflict toward job satisfaction. techniques of writing are through literature review and previous research findings. This article describes that role conflict as a part of role stressor is able to cause work stress. Work stress that can not be solved, it may decrease level of auditor’s satisfaction. Keywords: antecedent, role conflict, and job satisfaction